Peningkatan Hasil Belajar Melalui Pembelajaran Berdiferensiasi dengan Game Interaktif Educaplay pada Materi Pecahan Kelas II SDN Sunyaragi 1: Penelitian Tindakan Kelas - Shokhifah; Ikariya Sugesti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study is a Classroom Action Research (CAR) aimed at improving the learning outcomes of second-grade students at SDN Sunyaragi 1 in the topic of fractions through the implementation of differentiated instruction based on learning styles with the support of the interactive media platform Educaplay. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. In the pre-cycle stage, the researcher conducted initial cognitive and non-cognitive assessments to identify students' learning styles. In Cycle I, the instruction was still general without differentiation, and the Educaplay content was limited. In Cycle II, the researcher implemented differentiated learning based on visual, auditory, and kinesthetic styles, along with enriched content and exercises on Educaplay. The results showed an increase in learning mastery from 18.52% in the pre-cycle to 62.96% in Cycle I, and a significant improvement to 88.89% in Cycle II. These findings indicate that differentiated instruction supported by Educaplay effectively enhances student learning outcomes in the topic of fractions.